Adenocarcinoma arising from sacrococcygeal mature teratoma in an adult female: report of a case - Naoki eMatsumoto; Keisuke eUehara; Masataka eAndo; Junki eArimoto; Takehiro eKato; Hayato eNakamura; Tomoki eEbata; Masato eNagino (Frontiers in Oncology, 2014)
We report a case of adenocarcinoma arising from a sacrococcygeal mature teratoma in an adult female. A 62-year-old female was diagnosed with a presacral tumor 10 years ago. Pelvic computed tomography (CT) demonstrated a presacral heterogenous tumor, containing multiloculated cystic area and enhanced solid component with calcification. Percutaneous needle biopsy for the solid component of the tumor identified an adenocarcinoma and the patient was diagnosed as having a sacrococcygeal teratoma with malignant transformation. Abdominosacral rectal resection with sacral amputation at the upper edge of the S5 was performed. The pathological diagnosis was adenocarcinoma derived from a mature teratoma. The tumor cells had infiltrated the rectal wall. After 7 months, a follow-up CT demonstrated swelling of the right inguinal lymph nodes and a right inguinal lymphadenectomy was performed. Pathological examination showed metastatic lymph nodes. The patient is doing well 21 months after the second surgery, with no signs of recurrence.